Contemporary world cinema : Europe, the Middle East, East Asia and South Asia - Chaudhuri, Shohini (Edinburgh : Edinburgh University Press, 2005)
Since the start of the 1990s, despite tougher competition than ever before from Hollywood, a rebirth and flourishing of cinema has been taking place in parts of Europe, the Middle East, East Asia and South Asia. This book provides an overview of the cinemas of these regions.
This book provides an overview of the cinemas of Europe, the Middle East, East Asia and South Asia, interpreting some of the recent developments as strategic responses to globalisation. Highlighting transnational and cross-cultural structures, influences and themes
Introduction -- European cinema -- Scandinavian cinema -- Middle Eastern cinema -- Iranian cinema -- East Asian cinema -- Hong Kong cinema -- South Asian cinema -- Indian cinema.
Includes bibliographical references (pages 175-186) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Online resource; title from PDF title page (JSTOR, viewed March 5, 2021).
Keywords: Motion pictures; Cinematography; Motion Pictures; Cinéma.; cinematography; PERFORMING ARTS -- Film & Video -- General; Cinematography; Motion pictures; Filmkunst; 24.32 history of film art; Film -- Geschichte 2001 ff -- 0 Gesamtdarstellung; Motion pictures -- Middle East; Motion pictures -- East Asia; Motion pictures -- South Asia; Motion pictures -- Europe; Motion pictures and globalization; Globalization in motion pictures; Film -- historia -- 1990-talet -- sekelskiftet 2000.; Filmkunskap; Motion pictures; Motion pictures; Films